KARAKTERISTIK BUDAYA ORGANISASI KUAT SEBAGAI UPAYA MENINGKATKAN KINERJA INDUSTRI DI BATIK DANAR HADI SURAKARTA - Hakim, Lukman (Universitas Muhammadiyah Surakarta, 2015)
This study aimed to identify: (1) the characteristic of strong corporate culture (2) the role of strong corporate culture, (3) the values as basically to strong corporate culture in PT Batik Danar Hadi Surakarta. This study used a qualitative approach with a multicase study design using a phenomenological approach. Data collection techniques include in-depth interviews, participant observation, and study documentation. Data were analyzed repeatedly through the triangulation analysis. The object of this study are have work experience of more than 10 years and having job possision in PT Batik Danar Hadi Surakarta. Results obtained from this study states that of the ten character of organizational culture that are (1) creativity and innovative, (2) agresivity, (3) attention to detail, (4) full expertise, (5) outcome orientated, (6) humanity oriented, (7) team work system, (8) harmonity.